2020
DOI: 10.4067/s0717-95022020000200392
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal HIIT is More Efficient Than Moderate Continuous Training for Management of Body Composition, Lipid Profile and Glucose Metabolism in the Diabetic Elderly

Abstract: is more efficient than moderate continuous training for management of body composition, lipid profile and glucose metabolism in the diabetic elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
5
0
3
Order By: Relevance
“…These data are similar to an investigation carried out by Louzada and Cols 10 . They revealed that highintensity intermittent training is more effective than continuous work to improve the lipid profile since it significantly reduces cholesterol and triglyceride levels and increases significant high-density lipoprotein levels during 60 days of training.…”
Section: Discussionsupporting
confidence: 91%
“…These data are similar to an investigation carried out by Louzada and Cols 10 . They revealed that highintensity intermittent training is more effective than continuous work to improve the lipid profile since it significantly reduces cholesterol and triglyceride levels and increases significant high-density lipoprotein levels during 60 days of training.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that regular physical activity can reduce neurological risk factors such as dementia [49], Parkinson's disease [50], frailty [51], and AD [52], which improve the quality of life [53]. Increased expression, secretion and downstream signalling of neurotrophic factors (BDNF, VEGF, IGF-1), reduced inflammation [54], and cardiovascular improvement, such as reduced arterial stiffness and lowered blood pressure [55][56][57][58], and cardiovascular improvement, such as reduced arterial stiffness and lowered blood pressure [57,59] are some of the mechanisms that could explain exercise-induced neuroplasticity. Taken together, all of these effects can contribute to the development of positive brain health, as shown in numerous studies [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Mediante isso, diferentes autores inferem que a intensidade do exercício é o principal fator relacionado aos benefícios no metabolismo da glicose, com exercícios resistidos, sendo que os exercícios intermitentes de alta intensidade, promovem os aprimoramentos esperados para o exercício e com o menor tempo necessário para que os primeiros efeitos apareçam se comparados com exercícios contínuos de intensidade moderada, inclusive no que se refere ao sistema cardiovascular, sugerindo-se, inclusive, segurança na sua aplicabilidade (Louzada-Júnior, da-Silva, da-Silva, Castro & de-Freitas, et al, 2020;Research, Society and Development, v. 10, n. 10, e369101019032, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i10.19032 S Sylow, Kleinert, Richter, & Jensen, 2017;Viana , Naves, Coswig de Lira & Steele et al, 2019;Stavrinou, Bogdanis, Giannaki, Terzis & Hadjicharalambous 2018;Lira, dos Santos, Caldeira, Inoue, Panissa & Cabral-Santos et al, 2017;Marosi & Mattson, 2014). Desta maneira, exercício sistematizado, aplicado por ao menos 3 vezes na semana, com intensidade moderada ou alta, por ao menos 30 dias consecutivos quando intensos e 60 é uma eficiente medida para a diminuição da glicemia sanguínea (Gibala, Little, Macdonald & Hawley, 2012;Karlsen, Aamot, Haykowsky & Rognmo, 2017;Ringseis, Eder, Mooren & Krüger, 2015).…”
Section: Discussionunclassified
“…Os indivíduos portadores de DM, apresentam uma condição crônica de saúde, que exige cuidados permanentes para manutenção de sua qualidade de vida e controle metabólico, além de risco aumentado do desenvolvimento de diversas comorbidades, sugerindo-se a necessidade de desenvolverem habilidades de autocuidado para o manejo da sua condição (Louzada-Júnior, da-Silva, da-Silva, Castro & de-Freitas, et al, 2020).…”
Section: Introductionunclassified
See 1 more Smart Citation